The Effect of Pupil Size on Cone Contrast Sensitivity - Ali Almustanyir; Meznah S. Almutairi; Amal Aldrwish; Nabeela Hasrod; Bader A. Alqhtani; Tahani Alqahtani; Muteb Alanazi; Mansour Alghamdi; Essam Almutleb; Balsam Alabdulkader; Faisal Fakhouri; Mosaad Alhassan (Life)
Background: Measuring contrast sensitivity for each of the three cone types separately allows for a more precise and clinically valuable assessment of color vision. This study examined how pupil size affects cone contrast sensitivity (CCS). Methods: This study included 50 participants of equal gender. The mean age was 20.88 (±1.8) years. Using the ColorDx, a Landolt C stimulus of various sizes in an adaptive screening mode, we sequentially determined contrast sensitivity for long-, medium-, and short-wavelength stimuli. Two consecutive measurements were performed on participants, one with their natural pupil size (range 4–5 mm diameter) and, subsequently, with six artificial eye pupils (1 mm to 6 mm). Results: Generally, the 1 mm pupil size caused the greatest reduction in contrast sensitivity for two of the three cones. There was no significant main effect of sex (F = 0.96, df = 1, p = 0.32) on the log cone contrast sensitivity of the L-cone. However, pupil size had a significant main effect (F = 116.1, df = 6, p < 0.001). Within each sex, the log CCS was significantly reduced as the pupil size decreased compared with the normal pupil size. Conclusions: New technologies that assess individual cone pathway functions could potentially assist in identifying early or progressive conditions that may impact color vision pathways from the retina to the brain. Standardized protocols—such as controlled retinal illumination—are critical to avoid misinterpretation.